Energetic impact of reconstructed debris flow on the intensity and duration of growth disturbances in tree rings - Wang, Xueliang; Sun, Juanjuan; Zhang, Yong; Jiao, Qisong; Qi, Shengwen; Wang, Ran; Liu, Haiyang; Zhang, Mengjie (Frontiers in Earth Science, 2023)
A rare study on the quantitative relationship between the energetic impact of debris flows on the intensity and duration of growth disturbances of tree rings was carried out, partly due to a lack of feasible approaches and detailed field evidence. In this study, we first used a dendrogeomorphic technique to determine the age of a recent debris flow derived from historic landslide deposits at Qingyang Mountain (QYM) on the northeastern Tibet plateau. We acquired the quantitative data on the annual widths of tree rings in history and confirmed the influence of the debris flow rather than other factors (e.g., climatic events and inset outbreaking) in disturbing the growth of tree rings in a specific year. Using this approach, we determined that the age of the debris flow at QYM occurred in 1982, which was speculated to be triggered by the high monthly precipitation registered during July 1982. Subsequently, based on the boundaries of historic debris flow identified on remote sensing images before and after 1982 and the depth-integrated continuum model, we reconstructed the process of the 1982 debris flow and obtained the kinematic energy of the debris flow impacting the sampled trees. Based on the study, we observed that two growth disturbance patterns of tree rings influenced by the reconstructed 1982 debris flow were revealed, including growth suppression and asymmetric growth. We obtained a raw logarithm relationship between duration (i.e., lasting time for the disturbed tree rings to recover the initial width) and intensity of growth disturbances (i.e., growth suppression ratio of disturbed tree rings). We concluded that there is a negative exponential relationship between the simulated kinematic energy of debris flow impacting the disturbed trees and the time to recover the initial width of corresponding tree rings.